(untitled) (International conference on multidisciplinary science, 2023)
A number of positive changes that have taken place in the field of medicine and education in recent years are closely related to the unification of the activities of representatives of various fields in new directions in solving the issues of the fate of children with developmental problems. Early diagnosis of deviations from the norm in the child’s development, elimination of the consequences of the problem, rehabilitation, providing pedagogical support to children of early and younger ages with developmental problems in one way or another, and developing models of integration into general education institutions remains one of the urgent problems on the agenda.